Plan para la disminución de la huella de carbono mediante la adopción de prácticas sostenibles para la empresa palermo sociedad portuaria (2023)
The Caribbean port terminals are called to carry out their operations in coordination with the environmental dynamics of the area in which they are located. For Palermo Sociedad Portuaria the factors that contribute to the emission of CO2 have been identified, , after the identification, the collection of emissions information is carried out and the calculation of the Carbon Footprint (HC) for the years 2019 and 2020 continues, These analysis of, in common with the CEO, mitigation strategies that were viable for the port operation were generated, this viability was defined with the follow-up in the implementation of practices such as fuel reduction, waste composting and application of dacite rock powder.The strategies were based on the decrease in fuel consumption that at the end of five periods resulted in a decrease in emissions of 1,629 tonCO2eq; composting will reduce 2 tonCO2eq per year; Along the same lines, the application of shale rock in the selected operating areas decreased by 0.000089 tons of CO2eq in a period of 45 days. It is estimated that with the implementation of the three main measures to one year can be reduced 37 ton tonCO2eq, this value represents 2% of the HC in relation to the base year 2020. The research was based on the current reality of the operation of the port terminal, showing that the practices carried out and the proposals based on the current operational and environmental context of the port sector can be replicated to any other port terminal. To seek in the port sector the integrality of the concept of "green port and smart port".